Moderate pathogenic effect of ligophorus uruguayense (Monogenoidea, ancyrocephalidae) in juvenile mullet mugil liza (Actinopterygii, Mugilidae) from Brazil - Pahor-Filho, Eduardo [UNESP]; Klosterhoff, Marta C.; Marchiori, Natalia C.; Pereira Júnior, Joaber (FapUNIFESP (SciELO), 2017)
Monogenoidea pathogenic activity can elicit various histological responses in fish. Species of Ligophorus are specific parasites of mullets, and its relationship with host fish may result in a moderate pathogenic action. In order to ascertain this relationship, estuarine mullets (Mugil liza) were collected in an estuary, reared in laboratory, for three weeks, and forwarded for histological and parasitological analyses. Ligophorus uruguayense (Monogenoidea) infestation in the gills of the mullets was identified. The severe infestation by only one species of Monogenoidea may result from the specificity of these parasites to mullets. Mullets submitted to histological analysis exhibited respiratory epithelium detachment; mild, moderate and severe hyperplasia of the respiratory epithelium; atrophy; and telangiectasia of the gills. This is the first study reporting that mullets highly infested by Monogenoidea can show mild (100%) to severe (20%) gill changes with a distinct frequency of occurrence. Because of the high prevalence of mild alterations observed, it is possible to accept that L. uruguayense is moderately pathogenic to M. liza, even during high prevalence and intensity of infestation, as a result of its specificity.
Keywords: Aquaculture; Histological changes; Monogenoidea; Mugilidae; Parasitosis